Formulation of carteolol chitosomes for ocular delivery: formulation optimization, ex-vivo permeation, and ocular toxicity examination. (2nd October 2021) - Zafar, Ameeduzzafar; Alruwaili, Nabil K.; Imam, Syed Sarim; Alsaidan, Omar Awad; Alharbi, Khalid Saad; Yasir, Mohd; Elmowafy, Mohammed; Ansari, Mohammad Javed; Salahuddin, Mohammed; Alshehri, Sultan
Abstract: Background :Conventional delivery systems like solution and suspension are commonly used for the treatment of ocular diseases but have low corneal residence time and hence the duration of effect is limited. These drawbacks of conventional systems can be reduced by preparing bioadhesive chitosan (CH) coated noisome. Methods : Niosomes (NIM) of carteolol (CT) were developed by the thin-film hydration method and optimised by the Box-Behnken statistical design. Further, the optimised CT-NIM was coated with CH to enhance the ocular residence time . The optimised formulation was evaluated for vesicle size, entrapment efficiency, and in-vitro drug release and transcorneal permeation, histopathology, etc. Results : CT-NIM-opt showed the vesicle size and entrapment efficiency of 235 ± 3.54 nm, and 70.45 ± 0.87%, respectively. DSC spectra exhibited that CT was completely encapsulated into the CH-CT-NIM matrix. Drug release from CH-CT-NIM-opt was more sustained (68.28 ± 4.2%) than CT-NIM (75.69 ± 4.5% in 12 h) and CT solution (99.89 ± 2.8% in 4 h). The CH-CT-NIM-opt represented a strong bio-adhesion (89.76 ± 3.6%) than CT-NIM-opt (15.65 ± 3.4%). The permeation flux exhibited 1.13-fold higher permeation than CT-NIM and 3.23 fold than CT solution. The corneal hydration was found to be within the limit value. The histopathology study exhibited no structural damage to the cornea . HET-CAM results showed zero scores indicating no bleeding or haemorrhage. CH-CT-NIM-opt was found to be isotonic and exhibited good stability when stored at 4 °C for the stated duration of time. Conclusion : The above findings suggested that NIM can be a potential carrier for the delivery of CT with better ocular residence time.